Three new terpenoids from Chonemorpha megacalyx. Issue 3 (1st February 2022) - Yuan, Fang-Yu; Wang, Xiao-Ling; Wang, Shu-Qi; Shen, Tao; Ren, Dong-Mei; Lou, Hong-Xiang; Wang, Xiao-Ning
Abstract: Two new triterpenoids, 3 β -hydroxytirucall-7, 25-dien-24-one (1 ) and 3 β -acetoxytirucall-7, 23, 25-triene (2 ), along with one new sesquiterpenoid, alloaromadendrane-12 α, 14 β -dioic acid (3 ), were isolated from the vines and leaves of Chonemorpha megacalyx Pierre. Their structures were established on the basis of extensive spectroscopic data. Graphical Abstract: